Repeatability of Nest Site Selection of Green Turtles on Samandağ Beach - Bektaş Sönmez (Çanakkale Onsekiz Mart University Journal of Marine Sciences and Fisheries)
Nest site selection is a maternal effect on hatchling survival in species without parental care. Sea turtles depend on sandy beaches for nesting, and females perform nest site selection on the beach for the successful development of their embryos. This study investigated the repeatability of nest site selection on Samandağ beach, a major green turtle nesting beach in the Mediterranean. During the 2013 nesting season, the distance to the sea, distance to vegetation, horizontal distance, and nest depth of the first and second nests of females were recorded using a tagging method. Repeatability analysis was performed using the rtpR package in R. A total of 91 turtles were tagged, of which 36 were observed during their first and second nests. The highest repeatability was found for horizontal distance, followed by distance to vegetation and distance to the sea. In contrast, nest depth showed insignificant repeatability. This suggests that green turtles select nesting sites that are close to the vegetation line but far from the sea and sites that are very close in horizontal distance. The results of this study include the results of a single year nesting season. It is recommended that future studies be conducted in consecutive years to see the results of repeatability of nest site selection from year to year.